Odpowiedzi

Najlepsza Odpowiedź!
2010-04-08T19:39:26+02:00
A) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5 = 3x-4-5x-7
-2x-x-2x-3x+5x = -4-7-7+4+5
-3x = -9 /:(-3)
x=3

b) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4 = -2x+3-x-7
-x-2x+x+2x+x = 3-7-4+3+4
x= -1

c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8 = -3x+4-x+6
4x+x-2x+3x+x = 4+6+5+7-8
7x = 14 /:7
x =2

d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4 = 3x-1+2x-5-7+3x
2x-2x-3x-2x-3x = -1-5-7+4+4
-8x = -5 /:(-8)
x= 5/8 (pięć ósmych)
2010-04-08T19:40:02+02:00